Validation of a Malay Version of the Patient-Rated Wrist Hand Evaluation (PRWHE-MV) - KH, Teh; Saaid F, Mohamed; M, Arumugam; MRI, Rosli (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: The Patient-Rated Wrist Hand Evaluation (PRWHE) is a widely used measure of patient[1]reported disability, pain and appearance related to both hand and wrist disorders. It has been adapted cross[1]culturally worldwide but not in Malaysia. We performed a translation and cross-cultural adaptation of the PRWHE into a Malay version (PRWHE-MV) with assessed reliability and validity in patients presented with hand and/or wrist disorders. MATERIAL AND METHODS: PRWHE-MV was developed via translation and resolution of cultural discrepancies. A total of 83 patients (38 men, 45 women) with the mean age of 38 (SD 14) years and hand and/or wrist disorders completed both PRWHE-MV and the Malay version of Quick DASH during their first orthopaedic hand clinic follow up, and a second PRWHE-MV at 48 hours later. Intraclass Correlation Coefficient (ICC) was used to assess test-retest reliability of the PRWHE-MV while Cronbach’s alpha was calculated to assess the internal consistency. We tested the validity of PRWHE-MV against the Malay version of Quick DASH by calculating the nonparametric Spearman’s correlation coefficient between these two measures. RESULTS: There was no major cultural problems during the forward and backward translation of PRWHE, except for a minor change owing to cultural discrepancy in toilet hygiene. The Cronbach alpha PRWHE-MV was 0.978 (SEM = 5.5) at baseline and 0.979 (SEM = 5.35) at the second assessment. For the test-retest reliability, ICC was 0.99. There was a strong direct correlation between the scores for the PRWHE-MV and the Quick DASH (r = 0.916, p< 0.001). A majority of patients considered hand appearance somewhat important and were bothered in the past week. Their main concerns were gaining back normal hand function and subsequently returning to work. CONCLUSION: The PRWHE-MV showed high internal consistency, test-retest reliability and good validity in patients with hand and/or wrist disorders.